Experimental investigation of high temperature oxidation behaviour of steels exposed to air-fuel natural gas or hydrogen combustion atmospheres during reheating on a semi-industrial scale - Claudia Radünz; María Agustina Ravotti; Stefan Schwarz; Siegfried Schider; Daniel Marian Ogris; Julia Katharina Engel; Phillip Haslberger; Christoph Hochenauer (Journal of Materials Research and Technology, 2025)
In the future, steel products will be reheated for hot working using hydrogen instead of natural gas. This study investigated the differences in oxide scale formation between natural gas/air and hydrogen/air combustion at constant air-fuel-ratio. Samples of a hypo-eutectoid, eutectoid and hyper-eutectoid steel grade (dimensions: 30 × 30 × 50 mm, W × H × L) were exposed to the two atmospheres in a semi-industrial scale furnace for 180 min at three sample core temperatures (1100, 1200 and 1280 °C). Specific mass gain was calculated and the samples were metallographically examined. Switching the fuel increased scale formation depending on the steel. The exponential correlation between temperature and scale formation is more pronounced for the eutectoid and the hyper-eutectoid steel grade. Metallographic investigations revealed similar scale morphologies in both atmospheres, but with significant temperature dependence. The decarburization depth is atmosphere-independent. Thus, switching fuel does not negatively impact the properties of the steel substrate; it only increases scale formation during reheating.